HISTORIANS OF THE UNION - Ion Valer XENOFONTOV (Akademos: Revista de Ştiinţă, Inovare, Cultură şi Artă, 2020)
After the achievement of the Great Union in 1918, was formed a pleiad of historians who created and acted in unison with the major event in the history of the Romanians. In this sense, historians of certain national and universal value belong, such as Nicolae Iorga, Vasile Parvan, Constantin C. Giurescu, Silviu Dragomir, Alexandru Boldur and others. In an institutional framework, were create scientific approaches in the field of history that aimed at a history of the Great Romania; were elaborated synthesis works, etc.